Climate change impacts on flexible pavement design and rehabilitation practices. Issue 9 (2nd September 2021) - Haslett, Katie E.; Knott, Jayne F.; Stoner, Anne M. K.; Sias, Jo E.; Dave, Eshan V.; Jacobs, Jennifer M.; Mo, Weiwei; Hayhoe, Katharine
Abstract : Climate change poses a threat to the performance and resiliency of flexible pavement systems around the world and can lead to inadequate designs or shortened service life which, in turn, tax the already limited budgets of transportation agencies and increase user costs. This paper aims to provide a high-level overview of three common approaches (scenario-based, asset-based and hybrid) that can be used to incorporate climate change in pavement design and rehabilitation practices. Examples of each approach for a flexible pavement system are presented along with a discussion of their advantages and limitations. Additionally, select results from a pavement life cycle assessment (LCA) case-study comparing the use of simulated future climate projections instead of historical observed climate data is included to demonstrate impacts on maintenance and rehabilitation budgeting and planning. Current knowledge gaps and research needs are identified and discussed to promote future collaboration towards designing and maintaining more resilient flexible pavements under a changing climate.